On-Stage Playing Space As a Resource of Managers’ Professional Development - A. E. Rostovskaya (Управление)
The article is devoted to the activities of the Laboratory “Workshop stage action in the management” of the Department of control theory on the formation stage methodology in management education. Appeal to this modern practice gives the Manager a chance to be holistic in action and to work effectively in a modern crisis situation. The stage space of the game becomes the site of formation of organizational and managerial positions in a situation of uncertainty and learning resource is an organic action of one’s own physicality (body and voice). Stage methodology opens up a different horizon of management education towards organic management.